Pengaruh Beban Kerja Pegawai, Motivasi Kerja, dan Kompetensi Pegawai terhadap Prestasi Kerja Pegawai (Suatu Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Ayub Pariakan, Melki; A. Manafe, Henny; Sia Niha, Simon; Paridy, Anggraeny (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This review aims to be able to determine the hypothesis that results between variables, and so that it can provide benefits for writing subsequent scientific papers. The results of this scientific work emphasize that: 1) Employee workload has a positive and significant influence on employee performance; 2) Work motivation has a positive or significant impact on employee performance; 3) Work motivation has a positive and important influence on employee performance; 4) Employee workload, work motivation, and employee competence simultaneously have a positive and meaningful impact on employee performance.